In Vitro Evaluation of Antifungal Effects of Mineral Trioxide Aggregate and Portland Cement on Candida Albicans - Mohammadi, Zahed; Khademi, Abbas Ali; Ezoddini Ardakani, Fatemeh (Iranian Endodontic Journal, 2008)
INTRODUCTION: Candida Albicans (CA) is by far the most common yeast of oral infections, including endodontic infections. The aim of this study was to evaluate and compare the antifungal effect of white-colored mineral trioxide aggregate (WMTA) and Portland Cement (PC) using a tube-dilution test. MATERIALS AND METHODS: WMTA and PC were tested freshly mixed and after 24 h. The experiment was performed in 24-well culture plates. Fifty wells were used and divided into four experimental groups (freshly-mixed WMTA freshly-mixed PC, 24 h-set WMTA, and 24 h-set PC) of 10 wells each and control groups of five wells each. Plates of Sabouraud dextrose agar mixed with CA served as positive control and Sabouraud dextrose agar without CA served as negative control. Fresh inoculate of CA was prepared by growing an overnight culture from a stock culture. Aliquots of CA were then taken from the stock culture and plated on the agar compound of the experimental and control groups. All plates were incubated at 37°C for1h, 24 h, and 72 h. Growth of fungi was monitored daily by the presence of turbidity. Kruskal-Wallis test was used for data analysis. RESULTS: Findings showed that in the freshly mixed as well as 24 h-set WMTA and PC, fungal growth was observed during 1 h incubation; whereas by increasing the incubation time, no fungal growth was observed in 24 h and 72 h. CONCLUSION: It was concluded that WMTA and PC (freshly mixed and 24-h set) were effective against CA.